A study of piano pedagogy : its history, theory, psychology and practical application - Keeves, June Kelk (Rhodes University, Faculty of Humanities, Department of Music, 1984)
A discourse concerning the importance followed by a study of piano pedagogy; of piano teaching method, its history and general aspects of piano technique; a fully comprehensive method of piano teaching from the very earliest stages to the advanced; a discussion of various important selected concepts incorporated in the method which require particular emphasis; the application of certain concepts in the various style periods, such as dynamics, tempo, tempo rubato, pedalling, ornamentation, to the teaching of a piece; a discussion of the psychology of piano teaching and practising. All of these various branches of study are imperative in the training of the prospective piano teacher. (Preface)
Keywords: Piano -- Instruction and study; Piano -- Methods